Essential features of responsible governance of agricultural biotechnology - Hartley, Sarah; Gillund, Frøydis; van Hove, Lilian; Wickson, Fern (Public Library of Science, 2016)
Agricultural biotechnology continues to generate considerable controversy. We argue that to address this controversy, serious changes to governance are needed. The new wave of genomic tools and products (e.g., CRISPR, gene drives, RNAi, synthetic biology, and genetically modified [GM] insects and fish), provide a particularly useful opportunity to reflect on and revise agricultural biotechnology governance. In response, we present five essential features to advance more socially responsible forms of governance. In presenting these, we hope to stimulate further debate and action towards improved forms of governance, particularly as these new genomic tools and products continue to emerge.